Evaluation of optic nerve sheath diameter in acute stroke: pre- and post-thrombolytic assessment - Erdem Sivas; Nese Colak; Basak Bayram; Muhammet Kursat Simsek; Nuri Karabay; Vesile Ozturk (PeerJ)
Background Intracranial pressure increases due to ischemic infarction caused by stroke. This study aimed to evaluate the pre-thrombolytic and post-thrombolytic optic nerve sheath diameter (ONSD) measurements in predicting clinical outcomes and complications for stroke patients. Methods ONSD was measured on computed tomography (CT) scans. The average ONSD (aONSD) was calculated from the right and left eyes. Pre-thrombolytic (ONSD-0) and post-thrombolytic (ONSD-24) values were compared according to right vs left eye, stroke-affected side of the brain, presence of complications, and mortality. Results Ninety-three patients were enrolled; 52.7% were female, and the mean age of all participants was 76 years. The aONSD-24 values were higher than the aONSD-0 values (5.5 ± 0.7 mm and 5.3 ± 0.7 mm, respectively, p < 0.001). There was no significant difference between right and left measurements (right ONSD-0 5.3 mm vs. left ONSD-0 5.3 mm, p = 0.257; right ONSD-24 5.6 mm vs. left ONSD-24 5.5 mm, p = 0.146; and ∆right ONSD 0.23 mm vs. ∆left ONSD 0.22, p = 0.717) and between the stroke-affected side and non-stroke-affected side measurements (stroke-affected ONSD-0 5.2 mm vs. non-stroke-affected ONSD-0 5.2 mm, p = 0.292; stroke-affected ONSD-24 5.5 mm vs. non-stroke-affected ONSD-24 5.4 mm, p = 0.124; and ∆stroke-affected ONSD 0.23 mm vs. non-∆stroke-affected ONSD 0.23 mm, p = 0.569). Intracranial complications occurred in 14 (15%) patients. There was no difference in ONSD values between patients with and without complications (p = 0.338 for aONSD-0, p = 0.216 for aONSD-24, and p = 0.902 for ∆a ONSD). There was no significant difference between the aONSD-0 and aONSD-24 values of surviving and non-surviving patients (aONSD-0: 5.3 ± 0.7 vs. 5.0 ± 0.5, p = 0.345; aONSD-24: 5.5 ± 0.7 vs. 5.3 ± 0.4, p = 0.522; and p = 0.386 for ∆ aONSD). Conclusions ONSD values on 24-h brain CT scans were higher than admission values in acute stroke patients receiving thrombolytic therapy, irrespective of the right or left side, stroke-affected side, presence of complications, and mortality. However, ONSD is not a sufficient parameter for predicting complications and death.